IAS 38 intangible assets and firm performance: Empirical evidence from selected consumer goods manufacturing companies listed in Nigeria - Ebe, Cletus Oluwadare; Salawu, Rafiu Oyesola; Aguguom, Theophilus Anaekenwa (International Journal of Innovative Research and Scientific Studies, 2023)
This study examined the effect of International Accounting Standards (IAS) 38 intangible assets on the firm performance of selected consumer manufacturing companies listed in Nigeria. The study employed secondary data extracted from the published financial statements of the sampled 15 companies out of a population consisting of 20 selected consumer goods manufacturing companies listed in Nigeria using a purposive sampling technique. A firm observation of 220 participants over 11 years from 2011 to 2021 was used in the study. Descriptive statistics and inferential analysis were adopted in the data analysis. The study revealed that intangible assets had a positive and significant effect on earnings per share (EPS) and the return on shareholders funds (SHF). The study concluded that the firm performance of selected consumer goods manufacturing companies in Nigeria was significantly affected by IAS 38 intangible assets. These findings suggest that compliance with IAS 38 standards is critical as it further deepens the relevance and faithful representation of financial statements prepared in Nigeria.